The planetary garden. Where natural and human intertwine - Pico, Ramón (Journal of Architecture and Urbanism, 2018)
Spring 1935. After twenty-five years of fascination for heights and six of flying, stimulating experiences, Le Corbusier published Aircraft, a real “Manifesto for a New Era”, according to his own words. Even though Vers une architecture had limited the aeronaoutic model validity to the framework of housing and easthetics ten years before, the reference then was expanded to the city and its fitting within the natural framework, to the definition of a new global habitat in which public space became the focus.The flying experience allowed him to look into the past and find the subtle balance of man and nature. Revelation and rebellion at the same time. Thanks to the new visual as well as mental perspective provided by height, he would drive his reflec-tions towards “geoarchitecture”, a definitive, Humboldtian approach to Earth.His aerial observation of the Algerian M’Zab valley or the layout of the settlements along the Paraná crystallised both into texts such as Sur les quattro routes, Aircraft or Les trois établissements humains, and a series of proposals for Rio, São Paulo, Montevideo, Buenos Aires and Algiers. Epic adventures through which, and connecting with the interest of those geographers worried about reclaiming human action on the writing on the Earth through his “establishments”, Le Corbusier tackled the configuration of a new public space beyond the limits of the traditional city, claiming for a new planetary order. First published online 11 December 2016